Working in Hollywood : how the studio system turned creativity into labor - Regev, Ronny (University of North Carolina Press, 2018)
This work reveals an important untold story of an influential twentieth-century workplace. Ronny Regev argues that the Hollywood studio system institutionalized creative labour by systemizing and standardizing the work of actors, directors, writers, and cinematographers, meshing artistic sensibilities with the efficiency-minded rationale of industrial capitalism.
Keywords: Motion picture industry -- California -- Los Angeles -- History -- 20th century.; Motion picture industry -- California -- Los Angeles -- Employees.; Cinéma -- Industrie -- Californie -- Los Angeles -- Personnel.; Cinéma -- Industrie -- Californie -- Los Angeles -- Histoire -- 20e siècle.; BUSINESS & ECONOMICS -- Industries -- Media & Communications.; TECHNOLOGY & ENGINEERING -- Telecommunications.; HISTORY -- United States -- 20th Century.; Motion picture industry; Motion picture industry -- Employees; California -- Los Angeles; 1900-1999; History